2020
DOI: 10.1109/access.2020.3009021
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to Map the Research Articles’ Sections to IMRAD

Abstract: The amount of scientific publications is believed to get doubled every five-years. These publications are stored by citation indexes and digital libraries in the form of complete PDF or/and by extracting terms from these documents. This indexing behavior poses several challenges for the scientific community as well as for digital repositories in terms of handling the advanced requirements of a user. For instance, addressing queries like "Give me those papers that contain the term "Pagerank" in their result sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…History is excluded because the characteristic in the test set is based on the predicted results, which may cause the accumulation of errors and interfere with the evaluation of overall classification performance, so it is not adopted in our experiment. We further incorporate some potential characteristics mentioned by Ahmed & Afzal (2020), namely, the number of references, the number of figures, the number of tables, and so on, which are easy to be ignored. In order to simplify the number of additional characteristics, this paper views the sum of tables and figures as another characteristic introduced into the experimental exploration.…”
Section: The Construction Of Feature Vector Of Traditional Modelmentioning
confidence: 99%
“…History is excluded because the characteristic in the test set is based on the predicted results, which may cause the accumulation of errors and interfere with the evaluation of overall classification performance, so it is not adopted in our experiment. We further incorporate some potential characteristics mentioned by Ahmed & Afzal (2020), namely, the number of references, the number of figures, the number of tables, and so on, which are easy to be ignored. In order to simplify the number of additional characteristics, this paper views the sum of tables and figures as another characteristic introduced into the experimental exploration.…”
Section: The Construction Of Feature Vector Of Traditional Modelmentioning
confidence: 99%
“…They found that the Voting Feature Intervals algorithm performed best, and the best result of the accuracy value is 71.38%. Ahmed and Afzal (2020) thought that term-based literature retrieval could not meet special needs. For example, the current retrieval system cannot return the literature containing a specific term (e.g., "PageRank") in the structure of the results.…”
Section: Introductionmentioning
confidence: 99%